![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(x^4+2x^3+3x^2+2x+1.\)
\(=x^4+x^3+x^3+x^2+x^2+x^2+x+x+1\)
\(=x^4+x^3+x^2+x^3+x^2+x+x^2+x+1\)
\(=x^2\left(x^2+x+1\right)+x\left(x^2+x+1\right)+\left(x^2+x+1\right)\)
\(=x^2\left(x+1\right)^2+x\left(x+1\right)^2+\left(x+1\right)^2\)
\(=\left(x+1\right)^2\left(x^2+x+1\right)\)
\(=\left(x+1\right)^2\left(x+1\right)^2\)
\(=\left(x+1\right)^4\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(x^3-x^2-14x+24\)
\(=x^3-2x^2+x^2-2x-12x+24\)
\(=x^2\left(x-2\right)+x\left(x-2\right)-12\left(x-2\right)\)
\(=\left(x-2\right)\left(x^2+x-12\right)\)
\(=\left(x-2\right).\left[x^2+4x-3x-12\right]\)
\(=\left(x-2\right).\left[x\left(x+4\right)-3\left(x+4\right)\right]\)
\(=\left(x-2\right)\left(x+4\right)\left(x-3\right)\)
\(x^4+x^3+2x-4\)
\(=x^4-x^3+2x^3-2x^2+2x^2-2x+4x-4\)
\(=x^3\left(x-1\right)+2x^2\left(x-1\right)+2x\left(x-1\right)+4\left(x-1\right)\)
\(=\left(x-1\right)\left(x^3+2x^2+2x+4\right)\)
\(=\left(x-1\right).\left[x^2\left(x+2\right)+2\left(x+2\right)\right]\)
\(=\left(x-1\right)\left(x+2\right)\left(x^2+2\right)\)
\(8x^4-2x^3-3x^2-2x-1\)
\(=8x^4-8x^3+6x^3-6x^2+3x^2-3x+x-1\)
\(=8x^3\left(x-1\right)+6x^2\left(x-1\right)+3x\left(x-1\right)+x-1\)
\(=\left(x-1\right)\left(8x^3+6x^2+3x+1\right)\)
\(=\left(x-1\right)\left[\left(8x^3+1\right)+\left(6x^2+3x\right)\right]\)
\(=\left(x-1\right)\left[\left(2x+1\right)\left(4x^2-2x+1\right)+3x\left(2x+1\right)\right]\)
\(=\left(x-1\right)\left(2x+1\right)\left(4x^2+x+1\right)\)
\(3x^2-7x+2\)
\(=3x^2-6x-x+2\)
\(=3x\left(x-2\right)-\left(x-2\right)\)
\(=\left(x-2\right)\left(3x-1\right)\)
Chúc bạn học tốt.
![](https://rs.olm.vn/images/avt/0.png?1311)
a , 3x2 + 3y2 - 6xy - 12
= 3 ( x2 + y2 - 2xy - 4 )
= 3 ( x - y )2 - 22
= 3 ( x - y + 2 ) ( x - y - 2 )
![](https://rs.olm.vn/images/avt/0.png?1311)
\(1,9x^3-3x^2+3x-1\)
\(=3x^2.\left(3x-1\right)+\left(3x-1\right)\)
\(=\left(3x^2+1\right).\left(3x-1\right)\)
\(4,x^4-x^3-10x^2+2x+4\)
\(=x^4-3x^3-2x^2+2x^3-6x^2-4x-2x^2-6x-4\)
\(=x^2.\left(x^2-3x-2\right)+2x.\left(x^2-3x-2\right)-2.\left(x^2-3x-2\right)\)
\(=\left(x^2+2x-2\right).\left(x^2-3x-2\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
=x3+2x2+x+2x+2
=x(x2+2x+1)+2(x+1)
=x(x+1)2+2(x+1)
típ nha bn
![](https://rs.olm.vn/images/avt/0.png?1311)
\(x^4+3x^2-2x+3=\left(x^4-x^3+x^2\right)+\left(x^3-x^2+x\right)+\left(3x^2-3x+3\right)\)
\(=x^2\left(x^2-x+1\right)+x\left(x^2-x+1\right)+3\left(x^2-x+1\right)\)
\(=\left(x^2+x+3\right)\left(x^2-x+1\right)\)